Development of rare resistance‐associated variants that are extremely tolerant against NS5A inhibitors during daclatasvir/asunaprevir therapy by a two‐hit mechanism. Issue 12 (30th March 2016) - Uchida, Yoshihito; Kouyama, Jun‐ichi; Naiki, Kayoko; Sugawara, Kayoko; Inao, Mie; Imai, Yukinori; Nakayama, Nobuaki; Mochida, Satoshi
Abstract : Aim: The virologic characteristics of resistance‐associated variants (RAVs) developing in patients receiving dual oral therapy with daclatasvir/asunaprevir, including those with previous triple therapy with simeprevir, were evaluated. Methods: A total of 206 patients with genotype‐1b HCV infection, including 5 patients with previous simeprevir therapy, were treated with daclatasvir/asunaprevir for 24 weeks. Resistance‐associated variants in the NS5A regions at baseline and during/after therapy were evaluated using cycling‐probe real‐time polymerase chain reaction combined with direct sequencing. The dynamics of rare RAVs were also assessed using ultra‐deep sequencing. Results: A sustained virologic response (SVR12) was achieved in 180 patients (87%); the rates were 95% in patients without baseline NS5A‐RAVs and 83%, 59%, and 77% in those with hepatitis C virus (HCV) strains carrying NS5A‐L31M, NS5A‐Y93H/C, and NS5A‐R30Q/H/L mutations, respectively. A multivariate analysis revealed baseline NS5A‐R30Q/H/L mutation and NS5A‐Y93H mutations as significant factors associated with SVR12. Virologic failure developed in all 5 patients with previous simeprevir treatment, and rare RAVs (HCV strains with NS5A‐R30H, NS5A‐A92K, NS5A‐P29 del, and NS5A‐P32 del ) developed at virologic failure. Ultra‐deep sequencing revealed that HCV strains with NS5A‐P29 del or NS5A‐P32 del were absent at baseline and emerged within 4 weeks of dual oral therapy among the strains appearing after simeprevir administration. Conclusion: NS5A‐R30Q/H/L and NS5A‐Y93H mutations at baseline determined the therapeutic efficacy of dual oral therapy with daclatasvir/asunaprevir, but rare NS5A‐RAVs developed frequently in patients with previous simeprevir treatment. Such RAVs may develop in a two‐hit manner, with simeprevir altering the quasispecies of HCV strains in the NS5A regions, leading to the emergence of HCV strains with NS5A‐P29 del and NS5A‐P32 del during exposure to daclatasvir/asunaprevir.